Comparison between determination of second anaerobic threshold by respiratory compensating point and X-method in rowers - Stefanov, L. G. (Pedagogy of Physical Culture and Sports, 2022)
Background and Study Aim. The aim of this study is to verify the X-method for determining the second anaerobic threshold in rowers.Material and Methods. Twelve male athletes from the national rowing team of Bulgaria were tested. Participants performed a one-time graded incremental exercise test to exhaustion on a rowing ergometer. The workload were conducted on rowing ergometer system Concept 2, and spirometry system Clark C5. We obtained ventilatory indices, intensity and heart rate bred-by-bred for each participant, for each test stage. The anaerobic threshold was determined by two methods: 1) by the localization of the respiratory compensation point visually, after polynomial regression analysis of the trends for the dynamics of the ventilatory variables related to time and 2) by the X-method using the change in the ratio between heart rate and pulmonary ventilation. We compared the heart rate corresponding to the anaerobic threshold determined by both methods.Results. We found similar values for heart rate at the respiratory compensation point and the anaerobic threshold determined by the X-method for each of the investigated. The Shapiro-Wilk test showed a normal distribution of the two samples with a significance level of a = 0.05. Thus, the t-test for two paired samples showed a p-value of 0.202 at a = 0.05. We found a correlation coefficient r = 0.973 between the heart rate at the anaerobic threshold (determined by X-method) and the heart rate at the anaerobic threshold (detected at the respiratory compensation point). The Blant-Altman analysis showed that 95% of the points in the scatter plot lie within the confidence interval.Conclusions. The two methods give similar results and can be applied alternatively in the investigation of rowers in the age group 18.3 ± 1.07 years. The X-method always gives a reliable intersection point, which in our studies is close to the second anaerobic threshold. Comparative studies are also needed in other contingents for the wider use of the X-method.